Respuesta :

Answer:

Step-by-step explanation:

f⁻¹(x) is the inverse of f(x).

y = 4x − 9.  To find the inverse, switch x and y and solve for y.

x = 4y − 9

x + 9 = 4y

y = (x + 9) / 4

So the inverse function is:

f⁻¹(x) = (x + 9) / 4

ANSWER

[tex]{f}^{ - 1}(x) = \frac{x + 9}{4} [/tex]

EXPLANATION

The given function is

f(x)=4x-9

Let

y=4x-9

Interchange x and y.

x=4y-9

Add 9 to both sides,

x+9=4y

Divide both sides by 4

[tex] \frac{x + 9}{4} = y[/tex]

[tex]y = \frac{x + 9}{4} [/tex]

Therefore,

[tex] {f}^{ - 1}(x) = \frac{x + 9}{4} [/tex]